KONTRUKSI VERBA SERIAL BAHASA DAYAK KENYAH LEPO’ TAU - Dicky Romadhan, Ahmad (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2020)
This study discusses the construction of serial verbs in the Lepo Dayak Kenyah language 'Tau. This research is a qualitative descriptive type. The data in this study were taken from native Lepo Dayak Kenyah speakers. The collection technique uses the listening technique and notes accompanied by elicitation techniques. The results of this study state that the construction of serial verbs in the Lepo 'Tau Dayak Kenyah language has the same characteristics as the extensive serial verb construction typology. In this study also found several semantic types in the construction of serial verbs in the Lepo 'Tau Dayak Kenya language, namely type of movement, directional type, type of type, cause-effect type, type of modality and type of aspect.